Demographic Dividend in Sub-Saharan Africa (SSA): A Far-Fetched Dream? - Onyekwere, Sixtus Cyprian (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This research was set out to assess whether ‘demographic dividend’ is a far-fetched dream for most countries in Sub Saharan Africa. To achieve this aim, the research draws from a wide range of secondary sources, including data from publications as well as past research and evidence gathered from this study shows that the Sub-Saharan Africa (SSA) region is still at the early stage of demographic transition thereby lagging when compared to other regions. The research concluded by aligning with the position that achieving demographic dividend may be a far-fetch dream for most countries in the Sub Saharan African region. Some policy recommendations were made with key emphasis on education, dulling out of modern and safe contraception, bridging the gap of gender inequality and investing in social amenities.